Heterotic groups of onions (Allium cepa L.) for the development of low-pungency hybrids - Saraiva, Fátima Rosangela de Souza; Melo, Rita Carolina de; Cerutti, Paulo Henrique; Coimbra, Jefferson Luís Meirelles; Alves, Daniel Pedrosa; Guidolin, Altamir Frederico (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2022)
The growing demand for low-pungency cultivars onion has opened new market niches. The objective of this study was to characterize heterotic onion groups to develop low-pungency hybrid cultivars. A field experiment with a randomized block design and two factors (genotype and fertilization) arranged in split plots was carried out in Ituporanga-SC (Brazil), in 2019. The plots corresponded to two fertilization levels (with and without sulfur), and the subplots corresponded to 26 onion genotypes, where the germplasm was derived from different (male-sterile-LA and maintainer-LB) lines, advanced populations and cultivars. The bulbs were evaluated for the following traits: pyruvic acid (indicator of pungency), sulfur content and bulb yield. The genotype performance differed according to the fertilization level. In the sulfur-free treatments, four heterotic groups were identified. The genetic variation in the crosses LA11 × LB24 and LA15 × LB19 could be exploited for negative selection for pungency and positive selection for bulb yield.